2011
DOI: 10.1002/yea.1892
|View full text |Cite
|
Sign up to set email alerts
|

Ferric reductase genes involved in high‐affinity iron uptake are differentially regulated in yeast and hyphae of Candida albicans

Abstract: The pathogenic yeast Candida albicans possesses a reductive iron uptake system which is active in iron-restricted conditions. The sequestration of iron by this mechanism initially requires the reduction of free iron to the soluble ferrous form, which is catalysed by ferric reductase proteins. Reduced iron is then taken up into the cell by a complex of a multicopper oxidase protein and an iron transport protein. Multicopper oxidase proteins require copper to function and so reductive iron and copper uptake are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 62 publications
0
26
1
Order By: Relevance
“…In contrast, addition of copper restored melanin production in the fre4⌬ mutant, as seen in other melanin-negative or -deficient mutants of C. neoformans: e.g., mel1, mel5, mel7, vph1, and clc-a mutations (47)(48)(49)(50). Ferric reductases are also known to reduce copper at the cell surface, as reported in S. cerevisiae and C. albicans (18,22,34). It is therefore possible that Fre4 in C. neoformans is a multifunctional enzyme with the ability to reduce copper, and thus its loss resulted in a defect in copper uptake and subsequently affected laccase activity.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…In contrast, addition of copper restored melanin production in the fre4⌬ mutant, as seen in other melanin-negative or -deficient mutants of C. neoformans: e.g., mel1, mel5, mel7, vph1, and clc-a mutations (47)(48)(49)(50). Ferric reductases are also known to reduce copper at the cell surface, as reported in S. cerevisiae and C. albicans (18,22,34). It is therefore possible that Fre4 in C. neoformans is a multifunctional enzyme with the ability to reduce copper, and thus its loss resulted in a defect in copper uptake and subsequently affected laccase activity.…”
Section: Discussionmentioning
confidence: 61%
“…However, the molecular genetics of the enzymatic reduction of ferric to ferrous iron have not been investigated for this pathogen. Ferric reductases are present in all fungal species, with variable numbers predicted across fungal genomes; these enzymes have been studied extensively in S. cerevisiae and, to some extent, in C. albicans, S. pombe, and A. fumigatus (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)42). In our study, we identified eight candidate ferric reductase (FRE) genes in C. neoformans, characterized their expression and contributions to reductase activity, and investigated their roles in virulence factor production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This enzyme degrades host erythrocytes to release iron for use in growth and metabolism of these fungi in cases of systemic infections. 16 We also compared the ability of C. albicans and non-albicans Candida species isolated from the oral cavity of HIV-positive patients to produce hemolysin. C. albicans is the predominant species associated with mucosal and systemic fungal infections.…”
Section: Discussionmentioning
confidence: 99%